PENGEMBANGAN MEDIA PERMAINAN ULAR TANGGA DALAM PEMBELAJARAN SEJARAH KERAJAAN-KERAJAAN ISLAM NUSANTARA DI SMA N 4 TANJUNG JABUNG BARAT - Azis Arman, Muhammad; Aprianda, Herti (Istoria: Jurnal Ilmiah Pendidikan Sejarah Universitas Batanghari, 2024)
This research and development originated from problems that arose at SMA N 4 Tanjung Jabung Barat, namely tending to like to play and not paying attention to teachers so that the material delivered by teachers could not be received properly. This study aims to determine the development of snakes and ladders game media and determine the feasibility of snakes and ladders game media. The development model used is ADDIE which has five stages, namely the analysis stage, design stage, development stage, implementation stage, evaluation stage. The snakes and ladders game media developed was then assessed by media experts and material experts. Based on field trials, the scores obtained were in the first trial of "72%" with the criteria of "Good", in the second trial of "75%" with the criteria of "Good", and in the third trial of "81%" with the criteria of "Very Good". So, it can be concluded that the medium of snakes and ladders game is "feasible" to use for students.